An Evaluation of the Rheumatology Periodical Literature used in Britain and the USA - THORPE, P. (Methods of Information in Medicine, 1972)
An application of the Gross and Gross method for the evaluation of periodicals to the literature of rheumatology used by workers in the UK and USA, has shown that a relatively small number of English language periodicals, the majority of which are not specialist rheumatology ones, contain a high percentage of the relevant papers.It is hoped that this data will be of value in the organization and administration of medical libraries and information units, and useful to the rheumatologist anxious to regularly scan those periodicals which are potentially of the most use to him.
Keywords: Rheumatology Literature; Usage of Periodicals; Library Organization